Enhancement of mass transport in fuel cells using three-dimensional graphene foam as flow field. (1st March 2018) - Park, Ji Eun; Lim, Jongkoo; Kim, Sungjun; Choi, Insoo; Ahn, Chi-Yeong; Hwang, Wonchan; Lim, Myung Su; Cho, Yong-Hun; Sung, Yung-Eun
Abstract: Graphene foam is a three-dimensional graphene-based material with interconnected macropores and it combines the advantage of graphene and structural characteristics of metal foam. Various kinds of metal foam have been developed as flow fields because their high porosity distributes reactants in an entire area and removes generated water. However, metal foam is highly susceptible to corrosion under the operating conditions of polymer-electrolyte-membrane fuel cells. In this work, we proposed using graphene foam as a flow field to investigate its effect on enhancing mass transport of reactants and products. Single-cell tests of the graphene-foam flow field showed the enhancement of mass transport, which led to increased performance at high current densities. Measurements of the oxygen gain (i.e., the difference in voltage under O2 and air atmospheres), electrochemical impedance spectra, and simulation results also revealed that the graphene-foam membrane-electrode assembly (MEA) exhibited lower mass-transport resistance than a conventional MEA because graphene foam is advantageous for the mass transport of reactants and water. Graphical abstract: Image 1 Highlights: A graphene foam MEA using graphene foam as flow field is proposed. The graphene foam MEA exhibits high cell performance, especially at high current densities. The graphene foam as flow field can decrease mass transport resistance.